Drastic enhancements of direct and indirect light emissions from Ge microbridge web-structures via efficient light confinements - Takahiro Inoue; Ayaka Odashima; Masaki Nagao; Kentarou Sawano (Applied Physics Express)
Drastic enhancements of both direct and indirect light emissions are demonstrated from Ge microbridge web-structures fabricated based on the strained Ge-on-Si (110) substrate. This enhancement is concluded to be caused more predominantly by the light confinement effect in several-μm-scale microbridges than the induced strain. It is also remarkable that this effect works very well with a strain as small as 0.4%, making the fabrication procedure very easy and bridges very stable and rigid. These findings will, therefore, widen the applicability and raise the potentiality of here-proposed Ge web-structure microbridges toward Si optical integrated circuits.